A foot in the door: Field experiments on entrepreneurs' network activation strategies for investor referrals. (5th October 2021) - Nai, Jared; Lin, Yimin; Kotha, Reddi; Vissa, Balagopal
Abstract: Research summary: We investigate entrepreneurial network activation—the processes by which entrepreneurs select specific contacts from their existing personal network and persuade the selected contacts to provide referrals to access targeted early‐stage investors (venture capitalists or angel‐investors). We differentiate between selection of entrepreneur‐centric contacts versus investor‐centric contacts. We also distinguish between persuasion tactics that induce contacts' cooperation through promises of reciprocity versus offers of monetary incentives. We conducted two field‐experiments in India and one in Singapore. Our primary field‐experiment involved 42 Singapore‐based entrepreneurs seeking referrals from 684 network contacts to reach a panel of four investors. Our evidence suggests that selecting investor‐centric contacts leads to greater referral success; in addition, persuasion by promising reciprocity also leads to greater referral success. Managerial summary: A vital first‐step for resource‐starved entrepreneurs seeking funding for their scalable business‐idea is to obtain referrals to early‐stage investors, because such investors pay more attention to referrals from trusted contacts. Using field‐experiments, we examine how entrepreneurs' choices in selecting network contacts and persuading them to provide referrals drive their access to investors. Results suggest that compared with the habitual pattern of requesting referrals from contacts proximate to themselves, entrepreneurs are about six times more likely to secure successful referrals when they select investor‐centric contacts for referral requests. Furthermore, actively persuading contacts by promising future reciprocity results in about three times higher likelihood of securing successful referrals. Our findings show how thoughtful activation of existing contacts can enable even modestly connected entrepreneurs to gain investor access.